El papel de las emociones en la enseñanza intercultural del español como lengua extranjera (ELE) - Spychała-Wawrzyniak, Małgorzata (Studia Romanica Posnaniensia, 2019)
Emotions, both positive and negative, are part of our lives. However, until the 1960s, little attention was paid to the role they played in learning foreign languages. It all changed with the development of humanistic psychology, which focused, among others, on the integration of cognitive and affective teaching. Emotions also accompany encounters of individuals representing two different cultures. Intercultural communication is a complex process, which often involves culture shock, conflicts and various types of interpersonal relations. The aim of this paper is to accentuate the role of emotions in foreign language teaching. We will put forward several proposals concerning affective learning viewed from the perspective of intercultural communication. Finally, we will present the results of the study conducted among learners of Spanish, which illustrates the importance of affective factors in constructing students’ positive attitudes towards language and culture.